IMPLEMENTATION OF THE CHILD-FRIENDLY MADRASAH PROGRAM IN PAI LEARNING TO ENHANCE STUDENTS' SPIRITUAL ATTITUDES - Sirajudin, Sirajudin; Malihah, Noor; Fauzan, Umar (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Background: This study examines the implementation of the Child-Friendly Madrasah Learning Program (MRAP) and its impact on enhancing students' spiritual attitudes. The MRAP program is designed to create a conducive environment for the holistic development of students, focusing not only on academic achievement but also on fostering positive spiritual and moral values. Purpose: The research aims to assess how MRAP influences students' spirituality, particularly in terms of self-awareness, empathy, and involvement in religious activities. Method: Using a qualitative case study approach, data were collected through observation, interviews, and document analysis. Result: The findings reveal that the implementation of MRAP significantly improves students' spirituality, as demonstrated by increased self-awareness, a greater sense of empathy towards others, and more active participation in religious practices. These results highlight the potential of MRAP as a model for integrating spiritual development within the educational framework. Conclusion: The study underscores the importance of incorporating spiritual aspects into educational programs to cultivate well-rounded individuals, providing valuable insights for educators in designing curricula that support both academic and spiritual growth.